The problem of social reabilitation of children-orphans with immaturity of intellectual development in the foreign and russian literature - V A Bichkov; V I Krasny (Peoples' Friendship University of Russia (RUDN University), 2009)
This article is devoted to discussion of a problem of social rehabilitation of children-orphans with the immaturity of intellectual development in the scientific literature. The maintenance of the term «rehabilitation» is considered into different theoretical aspects. The new contents of concept rehabilitation is offered as a system of the complex measures directed on preparation of the pupils of VIII type school of a kind to transition in the new environment (independent life) for high-grade functioning in society.